Lexical markers of evidentiality on vernacular malay dialect used by the speech community of kualuh - NUZWATY, NUZWATY (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The study talks about lexical markers of evidentiality used by the speech community of Bahasa Kualuh. The data was utterances dealing with lexical makers of evidentially that exist in the face to face communication and employed from ten native speakers who were 35-45 years old. It is found; the indicator of lexical markers of evidentiality evokes in two formulas: the first one is the quotative marker of evidentiality, supports the evidence-based under the speaker judgment, then he reports the result to the hearer, the second one is sensory evidential markers, which related to the evidential information based on human senses.